Homologous interference of lymphocytic choriomeningitis virus involves a ribavirin-susceptible block in virus replication. - Géssner, A (1989)
Depending on the multiplicity of infection (MOI), infection of L929 cells results in either productive lymphocytic choriomeningitis virus replication or homologous interference M. Bruns, A. Gessner, H. Lother, and F. Lehmann-Grube, Virology 166:133-139, 1988). As shown in this communication, productive lymphocytic choriomeningitis virus replication as observed at a low MOI was effectively inhibited by ribavirin. In contrast, virus yields increased if cells were infected with a high MOI and in the presence of 5 microM of the antiviral compound. This drug-dependent release of infectious virus was preceded by enhanced nucleoprotein (NP) synthesis, a change in intracellular NP distribution, and by an onset of glycoprotein synthesis. It is therefore proposed that this block in viral replication is brought about by a posttranslational effect on a viral gene product, probably the NP, present in reasonably large quantities both during homologous interference as well as persistent infection.